Effect of Pectin Variation and Sweet Orange (Citrus sinensis) Peel Extract on Bioplastic Synthesis - Matlubah, Uno Sheva; Tankoiko, Soghi; Alam, Yanuar Bakhrul; Andiarna, Funsu; Agustina, Eva; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2023)
Indonesia is the second largest country after China as a plastic user. The problems that occur regarding plastic waste require other alternatives by developing environmentally friendly plastics (biodegradable). One way to synthesize bioplastics is to use sweet orange (Citrus sinensis) peel pectin. The purpose of this study was to determine the bioplastic characteristics of pectin and the addition of orange peel extract with variations of 1%, 3% and 5% pectin to the resulting bioplastics and to determine the characterization of bioplastics through water absorption, tensile strength and elongation tests. Orange peel extract used as an additive for bioplastics was extracted using the maceration method with ethanol solvent. The results obtained were 0.9%, 1.7% and 3% water absorption, 1.106 and 0.9 MPa tensile strength, and 1. 8% and 0.49%.